2007
DOI: 10.1007/s11270-007-9520-z
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Chromium Removal by a Trichoderma inhamatum Fungal Strain Isolated from Tannery Effluent

Abstract: A fungal strain possibly capable of removing hexavalent chromium was to be isolated from industrial effluent from a leather factory located in the city of Guadalajara, state of Jalisco, Mexico. The strain was identified as Trichoderma inhamatum by the D1/D2 domain sequence of the 28S rDNA gene. Batch cultures of T. inhamatum in media containing initial Cr(VI) concentrations from 0.83 to 2.43 mM Cr (VI) were prepared. Experimental results suggest that the fungus is capable of transforming hexavalent chromium to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 52 publications
2
24
0
5
Order By: Relevance
“…By using desorption and X-Ray Photoelectron Spectroscopy (XPS) studies they showed that most of the Cr bound onto the biomass was in the trivalent form and postulated that the main mechanism of Cr(VI) removal was a redox reaction between Cr(VI) and the dead fungal biomass, which is quite different from previously reported mechanisms. It was also reported that Trichoderma inhamatum, grown in a batch culture system, exhibited a remarkable capacity to tolerate and completely reduce Cr(VI) to Cr(III) from initial concentrations of 0.83 up to 2.43 mM [56] and that the specific and volumetric rates of Cr(VI) reduction by this fungus decreased as the initial Cr(VI) concentration increased.…”
Section: Chromium Removal Via Uptake By the Fungal Biomassmentioning
confidence: 88%
“…By using desorption and X-Ray Photoelectron Spectroscopy (XPS) studies they showed that most of the Cr bound onto the biomass was in the trivalent form and postulated that the main mechanism of Cr(VI) removal was a redox reaction between Cr(VI) and the dead fungal biomass, which is quite different from previously reported mechanisms. It was also reported that Trichoderma inhamatum, grown in a batch culture system, exhibited a remarkable capacity to tolerate and completely reduce Cr(VI) to Cr(III) from initial concentrations of 0.83 up to 2.43 mM [56] and that the specific and volumetric rates of Cr(VI) reduction by this fungus decreased as the initial Cr(VI) concentration increased.…”
Section: Chromium Removal Via Uptake By the Fungal Biomassmentioning
confidence: 88%
“…La pared celular fúngica tiene diferentes grupos funcionales que pueden formar complejos de coordinación con los metales, lo que puede facilitar la remoción de los mismos en solución. Además, nuestras observaciones son similares a la mayoría de reportes de la literatura (Morales-Barrera y Cristiani- Urbina, 2008;Rodríguez et. al., 2008 También, se realizó un estudio de biorremediación, en el cual se inocularon 5 x 10 5 esporas/mL, a 100 mL de LMM (pH 5.3.)…”
Section: Resultados Y Discusiónunclassified
“…A las concentraciones analizadas (38, 76, y 114 mg de peso seco), la capacidad de remoción fue similar (99.17%, 97.95%, y 97.25%, respectivamente). En contraste a nuestras observaciones, la mayoría de los reportes en la literatura indican que a mayor cantidad de biomasa aumenta el porcentaje de remoción (Srivastava y Thakur, 2006;Morales-Barrera y Cristiani-Urbina, 2008;Rodríguez et. al., 2008), pues a mayor cantidad de inoculo, hay más sitios de unión para acomplejar el metal (por ejemplo, los iones HCrO -4 y Cr 2 O 7 -2 ) (Cervantes et.…”
Section: Resultados Y Discusiónunclassified
“…Además, nuestras observaciones son similares a la mayoría de reportes de la literatura (MoralesBarrera y Cristiani-Urbina, 2008;Rodríguez et. al., 2008).…”
Section: Información Tecnológica Vol 22 Nº 4 -2011 46unclassified
See 1 more Smart Citation